Economics of Adaptation to Climate Change : Ethiopia - World Bank (Washington, DC, 2013)
The report is part of a broader study, the Economics of Adaptation to Climate Change (EACC), which has two objectives: (a) to develop a global estimate of adaptation costs for informing international climate negotiations; and (b) to help decision makers in developing countries assess the risks posed by climate change and design national strategies for adapting to it. This paper is one of a series of country-level studies, where national data were disaggregated to more local and sector levels, helping to understand adaptation from a bottom-up perspective. Ethiopia is heavily dependent on rainfed agriculture. Its geographical location and topography in combination with low adaptive capacity entail a high vulnerability to the impacts of climate change. Historically the country has been prone to extreme weather variability. Rainfall is highly erratic, most rain falls with high intensity, and there is a high degree of variability in both time and space. Since the early 1980s, the country has suffered seven major droughts five of which have led to famines in addition to dozens of local droughts. Major floods also occurred in different parts of the country in 1988, 1993, 1994, 1995, 1996, and 2006. Climate projections obtained from the GCMs referred to above suggest an increase in rainfall variability with a rising frequency of both severe flooding and droughts due to global warming.